Spanish for nursing: A needs analysis for a Spanish for nursing course - Lindsay Helms; Hannah Pitner; Rebecca Adams (Revista de Lenguas para Fines Específicos, 2023)
Research has shown that language barriers can impede access to healthcare and impact healthcare outcomes. Traditional Spanish courses have been criticized for not effectively addressing learners’ specific needs, while Language for Specific Purposes (LSP) courses on healthcare frequently lack a credible methodological foundation. The current study uses a Task Based Language Teaching (TBLT) framework to conduct a needs analysis exploring the most vital Spanish language needs of nurses while also evaluating the effectiveness of previous language teaching in satisfying those needs. Surveys and interviews among 45 nurses and advanced nursing students show that the majority of participants recognized a need for healthcare-based Spanish instruction. The analysis uncovered specific linguistic features and real-world tasks designated as essential needs for nurses.